Colistin-niclosamide effervescent dry suspension combats colistin-resistant Salmonella in vitro and in vivo - Junkai Zhang; Qingqing Miao; Xiaoyuan Ma; Dandan He; Yushan Pan; Li Yuan; Yajun Zhai; Gongzheng Hu (Poultry Science)
The increasing incidence of bacterial infections caused by multidrug-resistant (MDR) Gram-negative bacteria has deepened the need for new effective treatments. It has been reported that niclosamide (NIC) can restore the sensitivity of Gram-negative bacteria to colistin (COL). However, NIC is practically insoluble in water and sparingly soluble in organic solvents, leading to limited therapeutic applications. This study aims to prepare a COL-NIC effervescent dry suspension (CNEDS) and evaluate its antibacterial effect against COL-resistant Salmonella both in vitro and in broiler chickens. With the sedimentation volume ratio as an index, suitable suspending agent, wetting agent, filler and effervescent agent were screened through a single-factor method. The preparation conditions were optimized using the Box-Behnken response surface method to obtain the formulation for CNEDS. The quality evaluation results showed that the successfully prepared CNEDS had a sedimentation volume ratio of 0.99, a drying weight loss of 1.3%, and a re-dispersion capability of 1-2 times, all of which met pharmacopoeial requirements. In terms of pharmacological evaluation, we first demonstrated that CNEDS substantially restored COL sensitivity against COL-resistant bacteria. Subsequently, time-killing analysis, scanning electron microscopy (SEM) and live/dead assays confirmed the antibacterial activity of CNEDS against COL-resistant bacteria. Finally, a Salmonella infection model in broiler chickens was established to further assess the therapeutic effect of CNEDS in vivo. CNEDS improved the survival rate of broiler chickens, reduced the bacterial burden on organs. These findings suggest that CNEDS effectively overcome COL resistance, indicating its potential for the treatment of COL-resistant bacterial infections in broiler chickens.